2023
DOI: 10.3390/plants12173101
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Arbuscular Mycorrhizal Fungi as Microbial Biostimulant, Sustainable Approaches in Modern Agriculture

Wenli Sun,
Mohamad Hesam Shahrajabian

Abstract: Biostimulant application can be considered an effective, practical, and sustainable nutritional crop supplementation and may lessen the environmental problems related to excessive fertilization. Biostimulants provide beneficial properties to plants by increasing plant metabolism, which promotes crop yield and improves the quality of crops; protecting plants against environmental stresses such as water shortage, soil salinization, and exposure to sub-optimal growth temperatures; and promoting plant growth via h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 452 publications
0
7
0
Order By: Relevance
“…Biostimulants are considered bioactive substances that are either inorganic or organic microorganisms that can increase crop performance when utilized in small quantities [ 1 ] as they can enhance both performance and growth as well as improve nutrient- and water-use efficiencies of different crops [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Amino acids have a dual function as building blocks for proteins and as providers of organic nitrogen, which can alleviate the negative impacts of drought and salt stress [ 9 ], and promote cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Biostimulants are considered bioactive substances that are either inorganic or organic microorganisms that can increase crop performance when utilized in small quantities [ 1 ] as they can enhance both performance and growth as well as improve nutrient- and water-use efficiencies of different crops [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Amino acids have a dual function as building blocks for proteins and as providers of organic nitrogen, which can alleviate the negative impacts of drought and salt stress [ 9 ], and promote cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AMF use in strawberry cultivation can function as an economically and environmentally viable fertilization technique [6].…”
Section: Introductionmentioning
confidence: 99%
“…Biostimulants can be used to complement the application of chemical inputs, including the utilization of beneficial rhizosphere microbiome like advantageous fungi and plant-growth-promoting rhizobacteria [ 1 , 2 , 3 ]. The major biostimulants effects on crops include improving the visual quality of final products, stimulating the immune systems of plants, inducing the biosynthesis of plant defensive biomolecules, removing heavy metals from contaminated soil, improving crop performance, reducing leaching, improving root development, improving seed germination, inducing tolerance to abiotic and biotic stressors, accelerating crop establishment, and promoting nutrient uptake and nutrient use efficiency [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that microbial biostimulants can synthesize IAA, which can promote root branching and plant growth of the plants under both abiotic and biotic stresses [ 4 , 5 ]. Microbial biostimulants can alleviate salt stress as they are associated with a high level of IAA and can improve them in the re-establishing of favorable water potential gradients under water shortage conditions as well as increasing film hydration around the roots [ 1 , 2 , 3 , 4 , 5 ]. Both PGPR and plants have ACC-deaminase, which has the ability to reduce the concentration of ethylene in the root zone and roots, with PGPR-derived ACC-deaminases being able to decrease ethylene-induced inhibition by reducing root zone ethylene [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%